ORGANIZATIONAL-METHODICAL FEATURES OF PROFESSIONAL SKILL IMPROVEMENT IN THE FORM OF DISTANCE LEARNING (Journal of Information Technologies in Education (ITE), 2010)
Results of the organization and modeling of training process at courses of staff qualification improvement with use of distance learning are presented. Experience of use of distance learning system «Kherson Virtual University» at courses of staff qualification improvement of the Kherson State University is described.
Keywords: distance learning; distance learning system «Kherson Virtual University»; improvement of professional skill of staff